LITERATURE REVIEW : PEMBERDAYAAN KESEHATAN MASYARAKAT PESISIR MELALUI TANAMAN MANGROVE - Arini Fajriani; Susilawati Susilawati (Kampurui Jurnal Kesehatan Masyarakat, 2023)
Community empowerment can be understood as an endeavor to restore or increase a group's capability so that they can exercise their rights and obligations as community members in a dignified manner. Mangroves are seen by residents of coastal communities as playing a significant role in the environment. Mangroves are a very promising plant because each portion may be utilized to make traditional remedies, in addition to protecting land from sea waves. The purpose of this study was to determine the function of mangrove plants as a health empowerment for coastal communities. The methodology used in this research is Systematic Literature Review (SLR). The data used in the research was sourced from the Google Scholar publication database, Neliti and Research Gate using the keywords "Community Empowerment", "Public Health Empowerment", "Coastal Community Empowerment" and "Mangrove Plant Benefits". Based on journal reviews, it can be concluded from several articles that mangrove plants have many functions and uses, especially in the health sector. Plants that are usually only used as abrasion prevention in coastal areas, are able to provide good properties for the body starting from the roots, skin, leaves, and fruit of these plants. The use of mangrove vegetation as traditional medicine has been trusted by coastal communities from hereditary knowledge and trials that have been carried out. It is hoped that this article can be used as material for further study and additional information in the field of health.